Chapter 1 Luxury and Indigenous Resurgence - Kucheran, Riley (Intellect, 2022)
Luxury and Indigenous Resurgence Riley Kucheran with Jessica P. Clark and Nigel Lezama In this discussion, Riley Kucheran, a member of Biigtigong Nishnaabeg (Pic River First Nation), shares his experiences and insights working with his community to promote artisanal production and land-based design education. This intervention highlights the current movement of Indigenous cultural resurgence that challenges hegemonic perceptions of the exclusive circulation of capital in settler-colonial and Eurocentric production systems. Kucheran sheds new light on how Indigenous making recentres both production and consumption and disengages the myth of the idealized creator-genius that typifies the cultural output of western modernity. Kucheran is an assistant professor of Design Leadership at Toronto Metropolitan University's School of Fashion.